Meeting the Civilised Barbarian: Bram Stocker's Dracula and Joseph Conrad's Hear of Darkness - Sara Martín (Miscelánea: A Journal of English and American Studies)
Even though there was no direct relationship between Bram Stoker and Joseph Conrad, there are sufficient grounds for a comparison between their two masterpieces, Dracula and Heart of Darkness, respectively. Both texts were first published in the same year, 1898, and"both voice similar concerns regarding the onset of the crisis of masculinity still making itself felt today and the position of Europe regarding the margins of the colonial world. Both Conrad and Stoker were aliens living in England, which lent an intriguing dimension to their views of the colonial and imperial question. These links have been recently stressed by the filming of Apocalypse Now (an adaptation of Heart of Darkness) and Bram Stoker's Dracula by the American director Francis Ford Coppola. Coppola has re-read the crisis of masculinity and the imperial question, transforming them into a valediction to the death of a form of patriarchal masculinity that he romanticises.